The orthodox arabs and Mar Saba monastery in the 16th and early 17th centuries (according to the data from arab christian manuscripts) - Konstantin Panchenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article deals with little-studied Christian Arab manuscripts of the 13th and 17th centuries from the collection of the Orthodox Patriarchate of Jerusalem associated with Mar Saba Monastery. In the 16th and early 17th centuries, this celebrated monastery was a centre of an autonomous monastic “republic”. It was polyethnic and alongside Balkan Slavs and Greeks, there were a number of Orthodox Arabs (the Melkites). For Syrian and Lebanese Orthodox people, this most important and the only survived monastery of the Judaean Desert remained a centre of high book culture, the most important point of attraction, a place where the dialogue between Orthodox cultures was going on, which in many respects stimulated the spiritual growth of the Melkites in the late 16th and 17th centuries. Contacts of Antiochian patriarchs, their milieu and ordinary pilgrims from Syria and Lebanon with Mar Saba Monastery, as well as the presence of Arab monks in the monastery, are refl ected in marginalia in a whole range of manuscripts given as presents to the monastery by Arab clergy- and laymen. Among the most interesting fi gures who left their notes on the margins of these books, one can name Patriarchs Yuwakim V ibn Juma (1543–1576) and Mikhail VI Sabbagh (1576– 1581/4), the monk of Mar Saba Yuhanna ibn Tashlak (later Metropolitan Yuwakim of Bethlehem), hieromonk Musa (the disciple of Patriarch Yuwakim ibn Juma), Cosmas ibn Dabbas (the future Patriarch of Antioch known as Cyril III, 1619–1628). The marginalia notes contain unique information on historical events of the Christian East and its spiritual life, on making books and their circulation, on cultural contacts of the Melkites in the 16th and early 17th centuries.